Manajemen Kemitraan Program Pintar Bersama Daihatsu Di SMK Negeri Rawas Ulu Kabupaten Musi Rawas Utara - Ratna, Parmi (UNIVERSITAS BENGKULU, 2024)
This study aims to describe the management of the smart program partnership with Daihatsu at Rawas Ulu State Vocational School including (1) the planning process (2) implementation, (3) evaluation and (4) follow-up. The method used in this research is descriptive qualitative, the research subject is the principal, class teacher and students, the instruments used in this research are interview guides, and observation sheets. The results of this study (1) Planning for a smart program with Daihatsu at Rawas Ulu State Vocational School with DUDI is based on curriculum synchronization, making an MoU and planning internship placements that are in accordance with student competencies (2) Implementation of a smart program with Daihatsu at Rawas Ulu State Vocational School practical activities industrial work, training for teachers and recruitment of graduates (3) Evaluation of the smart program with Daihatsu at Rawas Ulu State Vocational School is carried out based on the work program that has been carried out (4) Follow-up of the smart program with Daihatsu at Rawas Ulu State Vocational School improves competency quality and graduates so that can be used directly in the world of work.